PA01.15. ADR Kshasutra Kit - A Breakthrough in the Standardization of Ksharasutra - Dwivedi, Amarprakash (Medknow Publications & Media Pvt Ltd, 2012)
‘Ksharsutra’ can be defined as an Ayurvedic medicated thread (Cutting Seton) coated with herbal alkaline drugs. ‘Ksharasutra therapy’ has been described as a treatment of choice for the treatment of fistula in ano due to low recurrence rate (up to 3%). However, this unique para surgical procedure is not yet globally accepted basically due to lack of standardization in the Ksharsutra preparation process and poor acceptability by Modern surgeons due to lack of training& fear of Complications. Need for Standardization of Ksharsutra: Standardization of ‘Ksharsutra’ requires standardization in preparation process and quality standards including packaging, storage, labeling and developing scientific parameters for maintaining its uniform coating, pH, microbial check etc. What is ‘ADR Ksharsutra Kit‘?‘ADR Ksharsutra Kit’ is a disposable ‘Ksharsutra Applicator’ made up of HDPE. This Ksharsutra embedded device after UV treatment is kept in Airtight silver foil sachet. The Physico chemical Characters of Ksharsutra, its indication, manufacturing details along with its expiry date, etc. are labeled properly. Method of ‘ADR Ksharsutra’ Application: The tip of the ‘ADR Ksharsutra Applicator’ is introduced in the external opening and allowed to follow the track upto the internal opening situated in the anal canal. Once the tip comes out through the internal opening, cap is removed and the Ksharsutra is firmly held with artery forceps. After this, applicator’ is withdrawn (taken back) from outside opening. By doing this, the embedded Ksharsutra is automatically placed in the fistula track whose two ends are tied together. ‘ADR Ksharsutra’ has truly made the entire procedure very smooth and will be helpful in Globalization of Ksharsutra technique for fistula ablation & acceptable to modern surgeons.